Therapeutic vascularization in regenerative medicine. (10th January 2020) - Gianni‐Barrera, Roberto; Di Maggio, Nunzia; Melly, Ludovic; Burger, Maximilian G.; Mujagic, Edin; Gürke, Lorenz; Schaefer, Dirk J.; Banfi, Andrea
Abstract: Therapeutic angiogenesis, that is, the generation of new vessels by delivery of specific factors, is required both for rapid vascularization of tissue‐engineered constructs and to treat ischemic conditions. Vascular endothelial growth factor (VEGF) is the master regulator of angiogenesis. However, uncontrolled expression can lead to aberrant vascular growth and vascular tumors (angiomas). Major challenges to fully exploit VEGF potency for therapy include the need to precisely control in vivo distribution of growth factor dose and duration of expression. In fact, the therapeutic window of VEGF delivery depends on its amount in the microenvironment around each producing cell rather than on the total dose, since VEGF remains tightly bound to extracellular matrix (ECM). On the other hand, short‐term expression of less than about 4 weeks leads to unstable vessels, which promptly regress following cessation of the angiogenic stimulus. Here, we will briefly overview some key aspects of the biology of VEGF and angiogenesis and discuss their therapeutic implications with a particular focus on approaches using gene therapy, genetically modified progenitors, and ECM engineering with recombinant factors. Lastly, we will present recent insights into the mechanisms that regulate vessel stabilization and the switch between normal and aberrant vascular growth after VEGF delivery, to identify novel molecular targets that may improve both safety and efficacy of therapeutic angiogenesis. Abstract : Therapeutic angiogenesis, that is, the generation of new blood vessels by delivery of specific factors, is required both for rapid vascularization of tissue‐engineered constructs and to treat ischemic conditions. A better understanding of the physiological mechanisms of vascular growth is important to exploit its therapeutic potential and for the rational design of cell, gene, and protein therapy approaches.